Fungsi Motif Waku Bhulakoi dalam Relasi Hidup Suku Sentani di Kampung Ifale - Meggy Merlin Mokay (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to discuss the functions contained in motifs or carvings on WB. The theory used in this research is Paul Cobley's theory of semiotic studies. The research method used is ethnographic method and descriptive method. The result of the research is that Waku Bhulakoi functions to accompany traditional ceremonies and traditional dances. The meaning contained in WB is sacred. The symbols in the WB describe the sacrifices in creating traditional objects in culture. The WB shape is like a tube whose center is slightly inward as a barrier between the top and bottom. The top is covered with human skin. Motifs or carvings are formed based on the fact that the characters reveal a certain environment of events with the function of local wisdom relations. The function of motive is as a medium of communication and a medium of expression of life that is lived collectively. In conclusion, Waku Bhulakoi is the name of the traditional Sentani Klen Haesei musical instrument, Ifale Village. Tifa is sacred because the cover is made of human skin. Waku Bhulakoi has a functioning motive that can be interpreted. Keywords: Motive, Waku Bhulaikoi, Sentani